Climate Analysis Based on Remote Sensing - Fahmi Arief Rahman; Hadisah, Mukhtafatul; Suryawati, Sinar (University of Jember, 2025)
Climate was an important factor that greatly influenced human life and the environment. Remote sensing facilitated the monitoring, recording, and interpretation of climate data, which could be used for geographic reference–based decision-making. This study aimed to analyze climate components using satellite imagery data. The research was conducted in Mojokerto Regency from January to April 2024. The analyzed climate parameters included LST from Landsat 8 SR, RH and THI from ERA 5, rainfall from CHIRPS, and evapotranspiration from MODIS. All data were processed and analyzed on the cloud computing platform GEE. The analysis of 2023 satellite imagery showed that Mojokerto Regency’s climate, in terms of LST, was dominated by the medium class (57.4%), RH was classified as slightly dry (47.4%), THI indicated uncomfortable (too hot) conditions in 32.4% of the area, rainfall was generally low (72%), and evapotranspiration was low in 65.9% of the total area. The results of this study could be used to develop strategies for increasing vegetation cover, implementing environmentally friendly land management, and adopting climate adaptation measures to reduce the risk of environmental degradation.